A protocol for a proof-of-concept randomized control trial testing increased protein quantity and quality in ready-to-use therapeutic food in improving linear growth among 6-23-month-old children with severe wasting in Malawi - Potani, I; Daniel, AI; Briend, A; Courtney-Martin, G; Berkley, JA; Voskuijl, W; Vresk, L; Bourdon, C; Kathumba, S; Mbale, E; Bandsma, RHJ (Public Library of Science, 2023)
Introduction: Ready-to-use therapeutic foods (RUTFs) have successfully promoted recovery from severe wasting and increased treatment coverage. However, RUTFs do not sufficiently improve linear growth, leaving many survivors of severe wasting at risk of persistent stunting, which is associated with high mortality risk, poor child development and non-communicable diseases in adulthood. High protein quantity and quality can stimulate linear growth. Aim: The trial aims to assess whether higher-protein-RUTF leads to higher concentrations of markers of linear growth compared to standard RUTF among 6–23 months old children with severe wasting. Methods: We designed a higher protein quantity and quality RUTF for a proof-of-concept (PoC) double-blind randomized controlled trial. Outcomes: The primary outcome is a change in insulin-like growth factor-1 (IGF-1), a hormone positively associated with linear growth after four weeks of treatment. Secondary outcomes include changes in ponderal and linear growth and in body composition from baseline to eight weeks later; plasma amino acid profile at four weeks; acceptability and safety. Implications: These findings will help in informing the potential impact of increased protein in RUTF on linear growth when treating severe wasting towards conducting a larger clinical trial. Trial registration: The trial has been registered on clinicaltrial.gov (NCT05737472).